THE EFFECT OF BETA GLUCAN OF SACCHAROMYCES CEREVISAE ON THE DECREASE OF ALPHA SYNUCLEIN EXPRESSION IN THE BRAIN SUBSTANTIA NIGRA OF PARKINSON’S WISTAR STRAIN RATS (Rattus novergicus) MODEL INDUCED WITH ROTENONE - Rahayu, Masruroh; Kurniawan, Shahdevi Nandar; Husna, Machlusil; Hermawan, Hanestya Oky (Malang Neurology Journal, 2016)
Background. One of the regenerative therapy modalities in Parkinson is using the beta glucan effect contained in Saccharomyces cerevisae.Objective. To identify the effect of reduction in alpha synuclein expression on the brain substantia nigra in Parkinson's rat model after given Saccharomyces cerevisae. Methods. This research applied true experimental design by in vivo with draft randomized post test only controlled group design. The sample was divided into five groups, each of them consisted of 5 rats. Variables measured were the decreasing level of alpha synuclein. Results. There was a significant difference between positive control and negative control group.Conclusion. The addition of Saccharomyces cerevisae is able to lower the alpha synuclein expression in Parkinson’s Wistar strain rat models significantly with maximum at the dose of 72 mg/kgBB.